Life-Threatening Anaphylaxis due to Cerebrolysin® - Helmut Trimmel; Wolfgang Tauber; Martin Zikeli (Case Reports in Neurological Medicine)
In this case report, we describe a well-documented, severe anaphylactic reaction after intravenous administration of cerebrolysin, a neurotrophic agent derived from highly purified porcine brain tissue, consisting of peptides and free amino acids. Cerebrolysin has been in use for decades, in various neurological diseases, but especially stroke and traumatic brain injury, with the aim of enhancing cognitive performance. After administration of cerebrolysin to an 85-year-old male patient suffering from subacute stroke, he developed a fulminant anaphylactic reaction. Following institutional standards, vital functions were quickly restored. The anaphylactic reaction was clearly confirmed by laboratory tests. To date, only rare cases of anaphylaxis due to cerebrolysin have been published in the literature. The current report is intended to raise awareness for the possibility of such a reaction, given the widespread use of cerebrolysin in several indications in mostly critical patients. The case shows how a completely unexpected life-threatening situation can be successfully treated by targeted measures, if the situation is recognized quickly. In light of this event, we consider pathophysiology of allergic reactions and treatment guidelines.